METHODS OF DEVELOPING IDEOLOGICAL IMMUNITY AMONG YOUTH BASED ON THE SCIENTIFIC HERITAGE OF THE TERMIZIY SCHOLARS (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the influence of the scientific heritage of the Termiziy scholars on the development of ideological immunity among youth. Practical recommendations are also provided, and their essence is analyzed.